Advanced upcycling of agro-industrial co-products of corn via different microorganisms. (January 2023) - Fan, Weiwei; Huang, Xuhui; Liu, Kehan; Xu, Yongping; Chi, Zhanyou
Abstract: Reusing agro-industrial co-products has been the research focus of sustainable development worldwide. To upcycle ethanol by-product and corncob into a balanced nutritional feed for pigs, Aspergillus niger, Trichoderma reesei, Bacillus subtilis, Bacillus coagulans, and Candida utilis were employed and investigated their nutrition and flavor improving abilities. The results showed that fermentation effectively improved the total protein content of distillers dried grains with solubles (DDGS), and the highest increasing was 96.3%, by Aspergillus niger . The essential amino acids for pig growth, including lysine, isoleucine, threonine, arginine, and valine, were increased after Aspergillus niger fermentation, and it increased by 191%, 16.0%, 91.1%, 60.2% and 200%, respectively. The leucine content decreased by 44.5% after fermentation with Aspergillus niger . It provided an alternative solution for the problem of pig inhibiting digestion by high leucine content. The highest degradation rate of cellulose was 15.7% with Trichoderma reesei, while the highest degradation rate of hemicellulose was 19.4% with Aspergillus niger . Besides, the flavor of furanal in feed fermented by Aspergillus niger was increased, which would improve the feeding rate of pig since furanal is favorite for pigs. Consequently, co-fermentation of DDGS and corncob by Aspergillus niger or Trichoderma reesei have a better effect on nutrition and flavor. The results proved a viable way of producing nutritional-improved pig feed from agro-industrial co-products of corn. Highlights: The first limiting amino acid Lys was increased to 4%, 6.20 mg/g in fermented feed. The soluble carbohydrate was increased by 207.3% via A. niger fermentation . Furanal in feed improved to 14.2 ng/g, would be more favorable for pigs.